Habits of Mind and Mathematical Creative Thinking: Evidence from a Correlational Study in Integral Calculus - Siregar, Hesty Marwani; Solfitri, Titi (Actual Insight, 2025)
In an era of increasing societal complexity and rapid change, developing mathematical creative thinking has become a central challenge in mathematics education worldwide, particularly in cognitively demanding domains such as integral calculus. While conceptual understanding remains fundamental, research indicates that students’ engagement in creative mathematical problem solving is strongly influenced by dispositional and metacognitive factors. Among these, habits of mind are increasingly recognized as essential in supporting persistence, flexibility, and reflective thinking when students confront complex mathematical problems. This study investigates the relationship between habits of mind and mathematical creative thinking among undergraduate mathematics education students enrolled in an integral calculus course. Using a correlational research design, data were collected from 60 students through a habits of mind questionnaire and an open-ended mathematical creative thinking test assessing fluency, flexibility, and originality. The findings show that participants’ habits of mind and mathematical creative thinking were generally underdeveloped, with most students falling within moderate to low achievement categories. Correlation analysis revealed a very strong positive association between the two variables, indicating that students with more developed habits of mind tend to demonstrate higher levels of creative thinking in integral calculus. Habits of mind accounted for a substantial proportion of variance in students’ mathematical creative thinking, providing empirical support for their role as a dispositional foundation for creative thinking in advanced mathematics learning. These findings underscore the importance of instructional approaches that intentionally cultivate students’ habits of mind alongside conceptual understanding to foster sustained creative mathematical engagement.